Mechanical and microstructural properties of laser direct energy deposited 15–5 PH and SS 316L stainless steel. (2022) - Das, Tishta; Roy, Himadri; Lohar, Aditya K; Samanta, Sudip.K.
Abstract: In order to produce, a component by Laser- direct Energy Deposition (L-DED), the study of mechanical properties can be an important attribute. In this paper tensile properties and microstructural characteristics of Laser-direct Energy Deposited (L-DED) 15–5 precipitation hardening (PH) and 316-L grade stainless steel (SS) are evaluated. After depositing the samples by the L-DED process, it is cut and machined by Wire electrical discharge machine (W-EDM). The percentage of elongation of L-DED produced 15-5PH SS and SS 316-L were found to be lower than wrought material of SS. Accordingly, the scan pattern shows an observable effect on the tensile properties of the deposited samples. Defects such as porosity, delamination, etc. significantly reduce the ultimate tensile strength (UTS) and also lower the elongation value of L-DED produced SS samples in this study.